PANDANGAN ORIENTALIS KLASIK TERHADAP ISLAM DAN NABI MUHAMMAD: ANALISIS HISTORIS DAN IMPLIKASINYA - Budi Ichwayudi; Wiridtananda Widiastuti Melati; Maulana Firmansyah; Syabrowi (AL-BAYAN INSTITUTE, 2025)
ABSTRACT This article critically examines the classical Western Orientalist perspectives on Islam and the Prophet Muhammad through a historical and literature-based analysis. The background of this study highlights how, from the Islamic Golden Age to the modern era, Orientalist scholarship has frequently constructed negative and biased narratives that have shaped Western perceptions of Islam. The research aims to identify the political and theological motives underlying Orientalist discourse and to analyze the impact of these narratives on relations between Muslims and non-Muslims. The study employs a literature review method, focusing on the works of prominent Orientalists such as Ignaz Goldziher and Joseph Schacht, as well as broader literature on the development of Orientalism in hadith studies and the biography of the Prophet Muhammad. The findings reveal that classical Orientalists often portrayed Islam as a static, irrational, and inferior religion, frequently disregarding the internal diversity of Islamic traditions. These negative portrayals have reinforced stereotypes and prejudices within Western societies, significantly affecting social and political relations between the Islamic world and the West. The implications of this study underscore the importance of understanding the political and theological agendas behind Orientalist scholarship and call for critical responses from Muslim scholars to balance the discourse, correct public perceptions, and foster more constructive and equitable dialogue about Islam and the Prophet Muhammad on a global scale.